Site-Selective C(sp3)–H Functionalizations Mediated by Hydrogen Atom Transfer Reactions via α-Amino/α-Amido Radicals - Kaur, Jaspreet; Barham, Joshua P. (Synthesis, 2022)
Amines and amides, as N-containing compounds, are ubiquitous in pharmaceutically-active scaffolds, natural products, agrochemicals, and peptides. Amides in nature bear a key responsibility for imparting three-dimensional structure, such as in proteins. Structural modifications to amines and amides, especially at their positions α to N, bring about profound changes in biological activity oftentimes leading to more desirable pharmacological profiles of small drug molecules. A number of recent developments in synthetic methodology for the functionalizations of amines and amides omit the need of their directing groups or pre-functionalizations, achieving direct activation of the otherwise relatively benign C(sp3)–H bonds α to N. Among these, hydrogen atom transfer (HAT) has proven a very powerful platform for the selective activation of amines and amides to their α-amino and α-amido radicals, which can then be employed to furnish C–C and C–X (X = heteroatom) bonds. The abilities to both form these radicals and control their reactivity in a site-selective manner is of utmost importance for such chemistries to witness applications in late-stage functionalization. Therefore, this review captures contemporary HAT strategies to realize chemo- and regioselective amine and amide α-C(sp3)–H functionalization, based on bond strengths, bond polarities, reversible HAT equilibria, traceless electrostatic-directing auxiliaries, and steric effects of in situ-generated HAT agents.1 Introduction2 Functionalizations of Amines3 Functionalizations of Carbamates4 Functionalizations of Amides5 Conclusion
Keywords: C–H functionalization; hydrogen atom transfer; N-radical cation; α-amino radical; α-amido radical; photocatalysis; regioselectivity; late-stage functionalization